(untitled) (Polis (Santiago), 2018)
Premises of the standard economic paradigm strongly oppose the issues that pose doubts about the sustainability of economic growth. In the first part of this paper, it is argued that the pre-analytical vision of standard economics about the economic system as an isolated system has prevented most economists to acknowledge that permanent economic growth is not possible in a finite world, and thus to give some convincing answers to the global ecological crisis that began to appear in the mid twentieth century. The second part proposes that economic growth not only is not possible but it is also not desirable, since it is not necessarily related to well-being and people’s quality of life.